Between the chaos and for coming: a cross-reading of Nietzsche’s thought - Feiler, Adilson Felicio (2016)
The presente Nietzsche research show itself as an important factor to thing about the future of the socials institutions based about the dogmatic rules. Beyond of big sistems it shows the chaos, implanted by the nihilism, and front which draws the future of the dawning. However, falls the question by the scope of this dawning of the future; to extend to whitch it is able of bring optimismin the presence of nihilistic whirl. These pages intend bring some track to reflect about the paradox of the pessimismo of nihilistic chaos and the optimism of future. For both proceeds to a transversal lecture of Nietzsche, from the current state, passing by the critic, to culminate in its future.